1983
DOI: 10.1111/j.1365-2621.1983.tb14841.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fermentation Time on the Inositol Phosphates of Bread

Abstract: Bread was made by an AACC procedure using whole wheat flour and 70%-extraction wheat flour. Five different fermentation times were applied. Six inositol phosphates and inorganic phosphate were separated, identified and quantified in the bread. It was found that phytate decreased and the inorganic phosphate increased, with the largest decrease in phytate occurring during first 30 min of fermentation. The content in intermediate inositol phosphates also changed and it was only after considering their phosphorus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
34
1

Year Published

1991
1991
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 7 publications
1
34
1
Order By: Relevance
“…The results suggested that the inhibitory effect of IP 5 was five-sixths that of equimolar amounts of IP 6 , thus corresponding to the number of phosphate groups. The addition of IP 3 and IP 4 produced via acid-catalyzed hydrolysis slightly increased the iron solubility under simulated physiologic conditions, but it was found to be strongly dependent on pH, in contrast with the addition of IP 5 and IP 6 . Iron solubility decreased markedly when the pH was increased from 6 to 7, making the effect of IP 3 and IP 4 on iron absorption difficult to predict.…”
Section: Introductionmentioning
confidence: 90%
See 3 more Smart Citations
“…The results suggested that the inhibitory effect of IP 5 was five-sixths that of equimolar amounts of IP 6 , thus corresponding to the number of phosphate groups. The addition of IP 3 and IP 4 produced via acid-catalyzed hydrolysis slightly increased the iron solubility under simulated physiologic conditions, but it was found to be strongly dependent on pH, in contrast with the addition of IP 5 and IP 6 . Iron solubility decreased markedly when the pH was increased from 6 to 7, making the effect of IP 3 and IP 4 on iron absorption difficult to predict.…”
Section: Introductionmentioning
confidence: 90%
“…The addition of IP 3 and IP 4 produced via acid-catalyzed hydrolysis slightly increased the iron solubility under simulated physiologic conditions, but it was found to be strongly dependent on pH, in contrast with the addition of IP 5 and IP 6 . Iron solubility decreased markedly when the pH was increased from 6 to 7, making the effect of IP 3 and IP 4 on iron absorption difficult to predict. In a human study of iron absorption from different bread meals, a strong negative correlation was found between iron absorption and the sum of IP 3 , IP 4 , IP 5 , and IP 6 , suggesting that IP 3 and IP 4 also contributed to the negative effect on iron absorption (13).…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…The role of PA as a food anti-nutrient motivated research aimed at reducing the PA content of commonly eaten foods through food processing, genetic engineering, and plant breeding. For example, processing and fermentation during bread making, malting, and blanching can result in significant PA reduction [1][2][3][4]. Phytic acid and its salts are present at 0.5% to 5% (w/w) levels in edible legumes, cereal grains, oilseeds and nuts [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%